APLIKASI LOGIKA FUZZY MENGGUNAKAN METODE MAMDANI DALAM OPTIMASI PERENCANAAN PRODUKSI AYAM GEPREK : (Studi kasus di Warung Serbu, Jember) - Abduh Riski; Lilian Atino Eyta Makin; Ahmad Kamsyakawuni (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2023)
MSMEs have a very large role in the development of the Indonesian economy. MSMEs in the food sector are the largest sectors compared with other MSME sectors. Warung Serbu is one of the SMEs in the food sector, one of which is geprek chicken. Warung Serbu often makes production decisions that are not always right (optimal) for each period. Product stockpiling often causes losses, but companies often experience product shortages to meet customer demand. The Mamdani method can be used to determine decisions based on this problem. This method is based on fuzzy logic. The process of making decisions through the fuzzy logic of the Mamdani method consists of several stages: fuzzification, rule formation, fuzzy logic analysis (rule implications and composition), and defuzzification. A GUI program was used in the Matlab software to simplify the display. Based on June-September 2022 data, a MAPE percentage of 7.4% was obtained, while the company's MAPE value for the desired (optimal) production was 11.09%. The prediction for the number of geprek chickens in the June 7, 2022, period was 132 portions, with a total production cost of Rp. 824000,-;